2016
DOI: 10.1111/bcp.12980
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vasoconstriction induced by β‐adrenoceptor blockers: a systematic review and a network meta‐analysis

Abstract: AIMPeripheral vasoconstriction has long been described as a vascular adverse effect of β-adrenoceptor blockers. Whether β-adrenoceptor blockers should be avoided in patients with peripheral vascular disease depends on pharmacological properties (e.g. preferential binding to β 1 -adrenoreceptors or intrinsic sympathomimetic activity). However, this has not been confirmed in experimental studies. We performed a network meta-analysis in order to assess the comparative risk of peripheral vasoconstriction of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 81 publications
(88 reference statements)
0
11
0
4
Order By: Relevance
“…In the recent years, the use of pharmacogenomics witnessed important success in the improvement of healthcare by developing therapeutic treatment and predicting individual response [ 23 ]. Distribution of VIP variants exerts irreplaceable significance in pharmacogenomics knowledge [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, the use of pharmacogenomics witnessed important success in the improvement of healthcare by developing therapeutic treatment and predicting individual response [ 23 ]. Distribution of VIP variants exerts irreplaceable significance in pharmacogenomics knowledge [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These common polymorphisms were shown to confer a high risk towards over-anticoagulation, predisposing the individuals carrying these polymorphisms to hemorrhagic incidents [ 22 ]. In addition, a variable response to beta-blockers used in the treatment of hypertension, including propranolol [ 23 ], metoprolol, atenolol [ 24 ] and clopidogrel [ 25 , 26 ] was observed in patients of European and African origins which can trigger a stroke [ 27 , 28 ]. Other serious adverse outcomes of drugs in MetS are reported such as sudden death, bleeding events, myopathy, [ 2 , 20 , 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, non-selective β-adrenoceptor blockers are currently used as antihypertensive, anti-tachycardia and anti-arrhythmic drugs. However, they have a variable propensity to enhance peripheral vasoconstriction [ 183 , 184 ].…”
Section: The Potential Therapeutic Relevance Of the Monoaminergic Modmentioning
confidence: 99%
“…Regarding triggering/aggravating factors for RP, a recent systematic review suggested that beta-blockers differ in their tendency to exacerbate vasoconstriction and that those with intrinsic sympathomimetic activity can most likely be safely used in patients with RP. 10…”
Section: Recent Findings/points To Highlightmentioning
confidence: 99%